Synergistic effect in ultrafine PtNiP nanowires for highly efficient electrochemical hydrogen evolution in alkaline electrolyte - Chen, Qian; Wei, Bo; Wei, Yi; Zhai, Pengbo; Liu, Wei; Gu, Xiaokang; Yang, Zhilin; Zuo, Jinghan; Zhang, Ruifeng; Gong, Yongji (Applied catalysis. B, Environmental, 2022)
Platinum-based catalysts play an important role in electrochemical hydrogen evolution reaction, which is a renewable and clean way to produce H2. Herein, we have successfully synthesized the ultrafine PtNiP NWs with diameter less than 5 nm via a simple two-step hydrothermal reaction method. Impressively, the PtNiP NWs exhibit one of the best electrocatalytic activity toward HER under alkaline conditions, which can reach current density of 500 mA cm−2 only at the −0.153 V vs RHE with Tafel slop of only 30 mV dec−1. The DFT calculation results show synergistic effect of Pt, Ni and P atoms, where Ni atoms are conducive to the adsorption of H2O and P atoms are helpful for the dissociation of H2O, significantly improving kinetic processes of hydrogen evolution reaction. This work could be instructive and meaningful to design highly efficient and stable HER catalyst in alkaline condition for practical applications. [Display omitted] •Synthesis of the ultrafine PtNiP NWs with diameter less than 5nm.•A high performance can reach with a low loading of PtNiP NWs.•PtNiP NWs exhibit one of the best electrocatalytic activity toward HER under alkaline conditions.•The superior HER activities of PtNiP NWs is attributed to synergistic effect of Pt, Ni and P atoms.